ISLEX – en flersproget nordisk ordbog - Jónsdóttir, Halldóra; Úlfarsdótti, Þórdís (Nordiske Studier i Leksikografi, 2004)
The Icelandic-Scandinavian dictionary project ISLEX has been going on since 2006 and is now in its final stages. The outcome of the project is twofold. Firstly, a longawaited Icelandic-Scandinavian dictionary has been compiled, specially designed for the web and its features (e.g. sound, images, links). Secondly, the project has provided valuable experience in building up such work jointly in four countries, as the Icelandic source language is processed in Reykjavík and the target languages in Copenhagen, Bergen and Göteborg, respectively. The ISLEX dictionary describes modern Icelandic. It contains a range of collocations, idioms and examples of use, all of which are translated into the target languages: Danish, Norwegian (Bokmål and Nynorsk) and Swedish. ISLEX is thus a multilingual dictionary within which are contained four bilingual dictionaries. Moreover, the Faroese joined the editorial team at a later stage, so Faroese will become the fifth target language. The user interface offers search in both the source and target languages, as well as direct comparison between the target languages' equivalents. The project has possibilities for research that could benefit Nordic linguistic collaboration, and its material is also a good base for inter-Nordic projects in education and language technology.